PENGARUH BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA YAYASAN PESANTREN HIDAYATULLAH DEPOK - Gani Alfianto (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2023)
This study aims to analyze (1) the relationship between organizational culture and employee performance, (2) the relationship between compensation and employee performance, and (3) the combined relationship of organizational culture and compensation on the Hidayatullah Depok Islamic Boarding School Foundation. This research is quantitative and uses descriptive research methods. The data analysis method employs multiple linear regression, t-tests, and F-tests. The sample in this study consists of 134 individuals out of a total of 284 employees of the Hidayatullah Depok Islamic Boarding School Foundation. The sampling technique used is probability sampling with a saturated sampling technique. The results of this study indicate that the regression coefficient for the organizational culture variable (X1) is 0,685, meaning that if the organizational culture (X1) increases by one unit, employee performance (Y) will increase by 0,685 units, assuming other independent variables remain constant. The regression coefficient for the compensation variable (X2) is 0,651, meaning that if compensation (X2) increases by one unit, employee performance (Y) will decrease by 0,651 units, assuming other independent variables remain constant. The calculation results using the SPSS version 29 program show that the obtained adjusted R2 coefficient is 0,213 or 21%. This indicates that the percentage contribution of the influence of the independent variables, namely organizational culture and compensation, is 21%.